(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Comprehensive laboratory examination, including all major blood biochemical parameters and allowing to assess the function of the liver (ALT, AST, total bilirubin), kidneys (urea, creatinine), as well as the metabolism of carbohydrates (glucose), lipids (total cholesterol) and proteins (total protein) [3,4].